Pengaruh ekstrak melon terhadap kadar HbCO pada tikus Wistar jantan yang dipapar asap rokok - Yuyun Erlina Susanti; Bambang Wirjatmadi; Merryana Adriani (Jurnal Gizi Klinik Indonesia, 2017)
Background: Smoking is something that is usual for most Indonesian society, especially adult males. According to Riskesdas, smoking behavior of the population trends to increase. A previous study suggested that exposure to cigarette smoke produce CO bond to hemoglobin. Melon (Cucumis melo) contains antioxidants that prevent tissue damage.Objective: Analyze differences in levels HbCO Wistar male rats in treated and untreated extracts of melon.Method: The research was a laboratory experiment with the post test control group design and complete random design. The subjects were 25 male Wistar rats aged 3 months. Subjects were divided into 5 groups and each group received treatment for 28 days. Data of level HbCO was collected and analyzed by Anova One Way test at 95% confidence level.Results: The results showed a difference between the average levels of HbCO male Wistar rats (p value=0,000) treated and untreated extracts of melon.Conclusion: Melon extracts effect on decreasing the levels of HbCO due to exposure to cigarette smoke. There were differences in levels of male Wistar rats HbCO on treated and untreated extracts of melon and be given at a dose of 250 IU/day.